Efek Penggunaan ACE Inhibitor terhadap Perubahan Tekanan Darah dan Kadar Kalium pada Pasien Hipertensi dengan Komplikasi Gagal Jantung di RSUP Sanglah Denpasar - Lestari, Ni Kadek Santi (Jurnal Farmasi Udayana, 2020)
ACE inhibitors are the first choice therapy used in the treatment of hypertension with heart failure. In hypertension with heart failure, ACE inhibitors are given in combination with other antihypertensive agents such as diuretics or ?-bloker, and aldosteron antagonists. One of the side effect caused by the use of ACE inhibitors for a long time is hyperkalemia. Severe hyperkalemia in conditions of heart failure can cause cardiac arrest and heart rhythm disorders. The purpose of this study was to determine changes in blood pressure and potassium levels in hypertension patients with heart failure after receiving combination ACE inhibitor therapy. This study was an observational study, conducted retrospectively using the patient's medical record data at Sanglah Hospital Denpasar, the data was processed descriptively and analytically using the paired t-test and wilcoxon methods in SPSS 22 software. 35 patients who met inclusion and exclusion criteria were obtained this research. The results of statistical tests showed that the use of ACE Inhibitor combination therapy gave a significant decrease in systolic and diastolic blood pressure of p value <0.05, at potassium levels didn’t provide a significant change effect of p value> 0.05. The use of a combination of ACE Inibitor + ?-Bloker causes one patient suffering mild hyperkalemia.